ANALYSIS OF RICE FARMING PRODUCTION FACTORS IN PATTIRO VILLAGE, MARE DISTRICT, BONE REGENCY - Ismarani; Rianti, Marlia; Mahmud, Ernida (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Rice agriculture holds a crucial position in sustaining food availability. and supporting the economic prosperity of rural communities. The productivity of rice can be increased through effective and efficient management of production inputs. the study intends to investigate the variables impacting rice farming in Pattiro Village, Mare District, Bone Regency. Data were gathered using questionnaires, complemented by direct observations, interviews, and document analysis, and subsequently analyzed with the Cobb–Douglas regression model. Respondents were determined through the application of a simple random sampling method, resulting in a sample of 42 rice farmers. This study employed both primary and secondary data sources and applied a quantitative approach, conducted from March to May 2025. The outcomes revealed that, collectively, land area, seed quality, fertilizers, pesticides, and labor significantly affected rice production. Nevertheless, partial analysis demonstrated that only land area had a statistically significant effect, while seeds, fertilizers, pesticides, and labor did not show a significant influence on rice output in Pattiro Village, Mare District, Bone Regency